ARTIFICIAL INTELLIGENCE AS A MARKETING TOOL FOR COMPETITIVE ADVANTAGE MSEs GROCERY STORES - abdul azis; Binta Zulfia; Etty Soesilowati (POLITEKNIK LP3I JAKARTA, 2026)
Micro and Small Enterprises (MSEs) in the grocery store sector play a strategic role in the Indonesian economy but face increasingly intense competition in the digital era. The utilization of technology, particularly Artificial Intelligence (AI), has become an innovative solution to create competitive advantage and business sustainability. This study aims to develop and examine an AI-based marketing media prototype for grocery stores to enhance user acceptance and business competitiveness. The research employs a Research and Development (R&D) approach with a quantitative explanatory design using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through Likert-scale questionnaires from 97 respondents and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that usability and functionality have a positive and significant effect on user acceptance, with an R² value of 0.961, demonstrating a very strong explanatory power of the model. The developed SITOKEL.ID application prototype integrates AI features for providing store information, business legality services, and interactive location mapping. These findings suggest that the implementation of AI in grocery store marketing strategies can enhance user acceptance and has strong potential to create competitive advantage and business sustainability for MSEs in the era of Society 5.0.